Feasibility study of Omaha System in the construction of health education program for elderly patients with chronic obstructive pulmonary disease (奥马哈系统在老年慢性阻塞性肺疾病健康教育方案构建中的可行性研究) - YANG Yuanqin (杨元琴); YIN Cuihong (尹翠红); SHEN Xiaohong (申晓红); WU Sichao (吴思超); WANG Anxiu (王安秀) (中西医结合护理)
Objective To analysis the feasibility of building health education program for chronic obstructive pulmonary disease(COPD) in the elderly with the framework of Omaha System. Methods The medical records of 60 elderly COPD patients were analyzed retrospectively to classify and statistically compare the language of the medical records description with Omaha problem classification subsystem and intervention classification subsystem. Results There were 1348 entries describing nursing problems, symptoms and signs in 60 nursing records of elderly COPD patients, and 960 entries describing nursing measures, of which 1403 (60. 79%) were completely consistent with the Omaha system concept, 781 (33. 84%) were partially consistent, and 124 (5. 37%) were inconsistent. Conclusion The Omaha system articles can describe most of the clinical health problems in elderly COPD patients, and the relevant knowledge and skills of these health problems are particularly important for the disease management of elderly COPD patients. Therefore, the Omaha system can be used as a guide to build health education programs for elderly COPD inpatients, improve the quality of medical and health education, and optimize the management of elderly COPD patients. (目的 研究以奥马哈系统为框架构建老年慢性阻塞性肺疾病(COPD)健康教育方案的可行性。方法 回顾性分析60例老年COPD患者的病历资料并进行归类及统计, 比较病历记录描述与奥马哈问题分类子系统与干预分类子系统语言间的吻合程度。结果 60例护理记录中共描述老年COPD患者护理问题、症状和体征的条目1348条, 描述护理措施的条目共计960条, 其中1403(60. 79%)条与奥马哈系统之间概念完全吻合, 781(33. 84%)条部分吻合, 124(5. 37%)条不吻合。结论 奥马哈系统的条目能够描述老年COPD患者临床大部分健康问题, 这些健康问题的相关知识和技能对老年COPD患者的疾病管理尤为重要。因此, 可以奥马哈系统为指引, 构建老年COPD住院患者的健康教育方案, 提升医护健康教育质量, 优化老年COPD患者管理。)